Yes, We Khan: Diversity and De-Monsterization of Muslim Identities in ‘Ms. Marvel’ (2014–) - Andreassen, Anja Borg (Nordlit, 2019)
In 2014, Marvel comics introduced a new character to take over the mantle of the superhero identity Ms. Marvel. The new heroine is Kamala Khan, a 16-year-old girl born and raised in New Jersey. Khan is Marvel’s first Pakistani-American, Muslim superhero to headline her own comic book; as such, she represents a move towards diversification in a historically conservative, white and masculine genre. In addition, Kamala Khan comes into existence in a political and social context where the 9/11 attacks, the ‘War on Terror’, and Islamophobia continue to reverberate. This article explores how the Ms. Marvel comic functions as a critique of the ways in which social norms, stereotypes and prejudices have monsterized multicultural, Muslim identities, especially in the years following 9/11. Conducting analyses of Khan’s conflicted relationship to her own identities and issues concerning visibility and concealment, I explore how these negative framings affect her self-perception, and in turn her self-representation. Lastly, I aim to illustrate the ways in which the comic challenges monolithic and monstrous representations of Islam through its depiction of diverse, multicultural, Muslim identities.